Positive electrode material and preparation method thereof, positive electrode slurry, positive electrode plate, lithium ion battery and preparation method thereof

By coating lithium carbonate on the surface of the positive electrode active material of the lithium ion battery and reacting with lithium hexafluorophosphate to form a lithium difluorophosphate coating layer, the problem of insufficient addition of lithium difluorophosphate in lithium ion battery is solved, and the cycle stability of the battery is improved and Energy density.

CN119297221APending Publication Date: 2025-01-10HUIZHOU EVE POWER CO LTD +1
View PDF 0 Cites 2 Cited by

Patent Information

Application Number
CN202411284723.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-12
Publication Date
2025-01-10

AI Technical Summary

Technical Problem

The amount of lithium difluorophosphate is added directly to existing lithium-ion batteries, which leads to a sharp increase in the viscosity of the electrolyte and reduces the performance improvement effect.

Method used

The surface of the positive electrode active material is coated with lithium carbonate, and a lithium difluorophosphate coating layer is formed by reacting with lithium hexafluorophosphate in the electrolyte, which increases the amount of lithium difluorophosphate added in the battery, and controls the mass ratio of the positive electrode active material and lithium carbonate by controlling the and ball milling conditions to ensure effective coating and reaction generation.

Benefits of technology

It effectively increases the amount of lithium difluorophosphate added in the battery, generates a stable solid electrolyte membrane, reduces the electrode/electrolyte interface impedance, and improves cycle stability and energy density.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119297221A_ABST
    Figure CN119297221A_ABST
Patent Text Reader

Abstract

The invention provides a positive electrode material and a preparation method thereof, a positive electrode slurry, a positive electrode plate, a lithium ion battery and a preparation method thereof, the positive electrode material is applied to a battery, the battery comprises an electrolyte, the electrolyte comprises lithium hexafluorophosphate and an organic solvent, the positive electrode material comprises a positive electrode active substance and lithium carbonate, and the organic solvent comprises lithium hexafluorophosphate and lithium carbonate. The lithium carbonate is coated on the surface of the positive active material, and the mass ratio of the positive active material to the lithium carbonate is 1: (0.001-0.03). The surface of the positive active material is coated with a layer of lithium carbonate, the lithium carbonate can react with lithium hexafluorophosphate in electrolyte, and a lithium difluorophosphate coating layer is generated on the surface of the positive active material in situ, so that the addition amount of lithium difluorophosphate in the battery can be effectively increased, and the performance of the battery is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of batteries, and in particular to a positive electrode material and a preparation method thereof, a positive electrode slurry, a positive electrode sheet, a lithium ion battery and a preparation method thereof. Background Art

[0002] The energy density of lithium-ion batteries is mainly determined by the specific capacity and electrode potential of the positive and negative electrode materials, but its performance is closely related to the electrode / electrolyte interface properties. In order to improve the performance of lithium-ion batteries, electrolyte additives are often used to improve the electrode / electrolyte interface properties. As a commonly used electrolyte additive, lithium difluorophosphate can be oxidized and decomposed on the surface of the positive electrode to form a layer of thermodynamically and mechanically stable solid electrolyte film, which can not only inhibit the oxidative decomposition of the electrolyte, but also effectively reduce the electrode / electrolyte interface impedance and improve the cycle stability. However, due to the limited solubility of lithium difluorophosphate in the electrolyte, adding too much will lead to a sharp increase in the viscosity of the electrolyte, thereby reducing the effect of its performance improvement. Summary of the invention

[0003] The embodiments of the present invention provide a positive electrode material and a preparation method thereof, a positive electrode slurry, a positive electrode plate, a lithium ion battery and a preparation method thereof, which can improve the technical problem of the limited amount of lithium difluorophosphate directly added to the existing lithium ion battery.

[0004] In a first aspect, an embodiment of the present invention provides a positive electrode material for use in a battery, wherein the battery includes an electrolyte, the electrolyte includes lithium hexafluorophosphate, the positive electrode material includes a positive electrode active substance and lithium carbonate, the lithium carbonate is coated on the surface of the positive electrode active substance, and the mass ratio of the positive electrode active substance to the lithium carbonate is 1:(0.001-0.03).

[0005] In one embodiment, the molar ratio of the lithium hexafluorophosphate to the lithium carbonate is 1:(0.001-0.1).

[0006] In one embodiment, the surface basicity of the positive electrode material is 80 μmol·g -1 ~2000μmol·g -1 ; and / or

[0007] The volume fraction of particles with an average particle size of 0.1 μm-0.3 μm in the lithium carbonate is at least 40%.

[0008] In a second aspect, an embodiment of the present invention provides a method for preparing a positive electrode material, wherein the positive electrode material is applied to a battery, wherein the battery includes an electrolyte, wherein the electrolyte includes lithium hexafluorophosphate, and wherein the preparation method comprises the following steps:

[0009] A positive electrode active material and lithium carbonate are provided, and the lithium carbonate is coated on the surface of the positive electrode active material to obtain a positive electrode material.

[0010] In one embodiment, coating the lithium carbonate on the surface of the positive electrode active material comprises:

[0011] The lithium carbonate and the positive electrode active material are ball-milled.

[0012] In one embodiment, the ball milling time is 2h-8h, and the rotation speed is 60r / min-120r / min; and / or

[0013] The ball milling is carried out under the environmental condition of dew point temperature ≤-50°C.

[0014] In a third aspect, an embodiment of the present invention provides a positive electrode slurry for use in a battery, wherein the battery includes an electrolyte, wherein the electrolyte includes lithium hexafluorophosphate, and the positive electrode slurry includes:

[0015] The above positive electrode material or the positive electrode material prepared by the above method for preparing the positive electrode material, as well as a binder and a conductive agent.

[0016] In one embodiment, the positive electrode slurry further includes a dispersant, and the mass percentages of the positive electrode material, the binder, the conductive agent and the dispersant are (94-98): (0.8-5): (0.5-5): (0.1-0.5).

[0017] In a fourth aspect, an embodiment of the present invention provides a positive electrode plate for use in a battery, wherein the battery includes an electrolyte, wherein the electrolyte includes lithium hexafluorophosphate, and includes the above-mentioned positive electrode slurry.

[0018] In a fifth aspect, an embodiment of the present invention provides a lithium-ion battery, comprising: the above-mentioned positive electrode plate and an electrolyte, wherein the electrolyte comprises lithium hexafluorophosphate and an organic solvent.

[0019] In one embodiment, the molar ratio of the lithium hexafluorophosphate to the lithium carbonate is 1:(0.001-0.1).

[0020] In a sixth aspect, an embodiment of the present invention provides a method for preparing a lithium ion battery, comprising the following steps:

[0021] A lithium-ion battery preform and an electrolyte are provided. The lithium-ion battery preform comprises a packaged negative electrode plate, the positive electrode plate, a separator and a battery shell. The electrolyte is injected into the lithium-ion battery preform and allowed to stand to obtain a lithium-ion battery. The electrolyte comprises lithium hexafluorophosphate and an organic solvent.

[0022] In some embodiments, the standing temperature is 40°C-80°C, and the standing time is 12h-96h.

[0023] Beneficial effects of the embodiments of the present invention:

[0024] In an embodiment of the present invention, by coating a layer of lithium carbonate on the surface of the positive electrode active material, the lithium carbonate can react with the lithium hexafluorophosphate in the electrolyte to generate a layer of lithium difluorophosphate coating in situ on the surface of the positive electrode active material, thereby effectively increasing the amount of lithium difluorophosphate added in the battery, thereby improving the performance of the battery; during the first charging process, the lithium difluorophosphate on the surface of the positive electrode active material can be oxidized and decomposed to generate a relatively stable solid electrolyte membrane, thereby inhibiting the oxidative decomposition of the electrolyte on the positive electrode surface, and at the same time effectively reducing the electrode / electrolyte interface impedance, thereby improving the cycle stability of the battery; by controlling the mass ratio of the positive electrode active material to lithium carbonate, the lithium carbonate can be effectively coated with the positive electrode active material, thereby effectively forming a lithium difluorophosphate coating layer, and at the same time making the battery cell have a higher energy density. BRIEF DESCRIPTION OF THE DRAWINGS

[0025] In order to more clearly illustrate the technical solutions in the embodiments of the present invention, the drawings required for use in the description of the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For those skilled in the art, other drawings can be obtained based on these drawings without creative work.

[0026] Figure 1 This is the ion chromatography test result of the positive electrode plate immersion liquid after high-temperature standing in Example 1 of the present invention. DETAILED DESCRIPTION

[0027] The technical solutions in the embodiments of the present invention will be described clearly and completely below in conjunction with the drawings in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments in the present invention, all other embodiments obtained by those skilled in the art without creative work are within the scope of protection of the present invention. In addition, it should be understood that the specific implementation methods described herein are only used to illustrate and explain the present invention, and are not used to limit the present invention. In the present invention, unless otherwise specified, the directional words used, such as "upper" and "lower", generally refer to the upper and lower parts of the device in actual use or working state, specifically the drawing direction in the drawings; while "inside" and "outside" refer to the outline of the device.

[0028] The technical solution of this application is as follows:

[0029] In a first aspect, an embodiment of the present application provides a positive electrode material for use in a battery, wherein the battery includes an electrolyte, wherein the electrolyte includes lithium hexafluorophosphate, and the positive electrode material includes a positive electrode active substance and lithium carbonate, wherein the lithium carbonate is coated on the surface of the positive electrode active substance, and the mass ratio of the positive electrode active substance to the lithium carbonate is 1:(0.001-0.03).

[0030] In the present application, by coating a layer of lithium carbonate on the surface of the positive electrode active material, it can react with the lithium hexafluorophosphate in the electrolyte to generate a layer of lithium difluorophosphate coating in situ on the surface of the positive electrode active material, thereby effectively increasing the amount of lithium difluorophosphate added in the battery, thereby improving the performance of the battery; during the first charging process, the lithium difluorophosphate on the surface of the positive electrode active material can be oxidized and decomposed to generate a relatively stable solid electrolyte film, thereby inhibiting the oxidative decomposition of the electrolyte on the positive electrode surface, and at the same time effectively reducing the electrode / electrolyte interface impedance, thereby improving the cycle stability of the battery.

[0031] In the present application, the mass ratio of the positive electrode active material to the lithium carbonate is 1:(0.001-0.03), for example, it can be 1:0.001, 1:0.003, 1:0.005, 1:0.007, 1:0.009, 1:0.011, 1:0.013, 1:0.015, 1:0.017, 1:0.019, 1:0.021, 1:0.023, 1:0.025, 1:0.027, 1:0.029, etc. Within the range, lithium carbonate can be effectively coated with the positive electrode active material, thereby effectively forming a lithium difluorophosphate coating layer, and the battery cell has a higher energy density.

[0032] In some embodiments, the molar ratio of the lithium carbonate to the lithium hexafluorophosphate is (0.001-0.1):1, for example, it can be 0.001:1, 0.005:1, 0.007:1, 0.01:1, 0.02:1, 0.03:1, 0.04:1, 0.05:1, 0.06:1, 0.07:1, 0.08:1, 0.09:1, 0.1:1, etc.

[0033] In the present application, by controlling the amount of lithium carbonate, the lithium carbonate can be fully reacted to generate lithium difluorophosphate, thereby forming a lithium difluorophosphate coating layer, and at the same time, the amount of lithium hexafluorophosphate remaining in the electrolyte can be controlled, thereby effectively reducing the internal resistance of the battery, thereby improving the cycle stability of the battery. If the amount of lithium carbonate is too much, more lithium difluorophosphate will be generated, which will cause the concentration of lithium hexafluorophosphate in the electrolyte to decrease, thereby reducing the conductivity of the electrolyte, increasing the internal resistance of the battery, and thus reducing the cycle performance; if the amount of lithium carbonate is too much, there may be unreacted lithium carbonate, which will cause the internal resistance of the battery to increase and the cycle performance to decrease.

[0034] In some embodiments, in some embodiments, the surface alkalinity of the positive electrode material is 80 μmol vg -1 ~2000μmol·g -1 , for example, 100 μmol·g -1 , 300 μmol·g -1 , 500 μmol·g -1 , 700 μmol·g -1 , 900 μmol·g -1 , 1100 μmol·g -1 , 1300 μmol·g -1 , 1500 μmol·g -1 , 1700 μmol·g -1 , 1900 μmol·g -1 Etc. Within the above range, the content of lithium carbonate on the surface of the positive electrode active material can be controlled.

[0035] In some embodiments, the volume fraction of particles with an average particle size of 0.1 μm-0.3 μm in the lithium carbonate is at least 40%, the average particle size can be 0.1 μm, 0.12 μm, 0.15 μm, 0.17 μm, 0.2 μm, 0.22 μm, 0.25 μm, 0.27 μm, 0.3 μm, etc., and the volume fraction can be 40%, 50%, 60%, 70%, 80%, 90%, 100%, etc. In this way, the particle size of lithium carbonate can be made smaller, so that it can be better coated on the surface of the active material.

[0036] In some embodiments, the positive electrode active material includes at least one of lithium cobalt oxide, lithium nickel cobalt manganese oxide, lithium nickel cobalt aluminum oxide, lithium nickel cobalt manganese aluminum oxide, lithium manganese oxide, lithium nickel oxide, lithium iron phosphate, lithium manganese iron phosphate, and lithium-rich manganese.

[0037] In a second aspect, an embodiment of the present application provides a method for preparing a positive electrode material, wherein the positive electrode material is applied to a battery, wherein the battery includes an electrolyte, wherein the electrolyte includes lithium hexafluorophosphate, and the preparation method comprises the following steps:

[0038] A positive electrode active material and lithium carbonate are provided, and the lithium carbonate is coated on the surface of the positive electrode active material to obtain a positive electrode material.

[0039] The preparation method in this application is simple to operate, compatible with existing battery preparation processes, and has no special environmental control requirements.

[0040] In some embodiments, coating the lithium carbonate on the surface of the positive electrode active material comprises:

[0041] The lithium carbonate and the positive electrode active material are ball-milled.

[0042] In the present application, coating is performed by ball milling, which is simple to operate and easy to implement.

[0043] It can be understood that the particle size of lithium carbonate particles is smaller than that of the positive electrode active material. After ball milling, lithium carbonate can be coated on the surface of the positive electrode active material.

[0044] In some embodiments, the ball milling time is 2h-8h, for example, it can be 2h, 3h, 4h, 5h, 6h, 7h, 8h, etc., and the rotation speed is 60r / min-120r / min, for example, it can be 60r / min, 70r / min, 80r / min, 90r / min, 100r / min, 110r / min, 120r / min, etc.

[0045] In some embodiments, the ball milling is performed under an environmental condition with a dew point temperature ≤ -50°C, such as -50°C, -55°C, -60°C, -65°C, -70°C, -75°C, etc. In this way, the amount of moisture absorbed by the positive electrode active material from the environment can be controlled.

[0046] In a third aspect, an embodiment of the present application provides a positive electrode slurry, which is applied to a battery. The battery includes an electrolyte, and the electrolyte includes lithium hexafluorophosphate. The positive electrode slurry includes the above-mentioned positive electrode material, a binder and a conductive agent.

[0047] In some embodiments, the positive electrode slurry further includes a dispersant, and the mass percentages of the positive electrode material, the binder, the conductive agent, and the dispersant are (94-98): (0.8-5): (0.5-5): (0.1-0.5). Within the above range, the positive electrode sheet can have good processing performance and conductivity, and at the same time have a higher energy density.

[0048] In a fourth aspect, an embodiment of the present application provides a method for preparing a positive electrode slurry, wherein the positive electrode slurry is applied to a battery, wherein the battery includes an electrolyte, wherein the electrolyte includes lithium hexafluorophosphate, and the preparation method comprises the following steps:

[0049] The positive electrode material, a binder, a conductive agent, a dispersant and an organic solvent are provided, and the pretreated positive electrode active material, the binder, the conductive agent and the dispersant are mixed in the organic solvent to obtain a positive electrode slurry.

[0050] In some embodiments, the organic solvent includes one or more of ethylene carbonate, methylpropyl carbonate, propylene carbonate, butylene carbonate, dimethyl carbonate, diethyl carbonate, or ethyl methyl carbonate.

[0051] In a fifth aspect, an embodiment of the present application provides a positive electrode plate, which is applied to a battery. The battery includes an electrolyte, and the electrolyte includes lithium hexafluorophosphate, including the above-mentioned positive electrode slurry.

[0052] In a sixth aspect, an embodiment of the present application provides a method for preparing a positive electrode sheet, comprising the following steps:

[0053] A current collector and the positive electrode slurry are provided, the positive electrode slurry is disposed on the current collector, and dried to obtain a positive electrode sheet.

[0054] In some embodiments, disposing the positive electrode slurry on the current collector includes: coating the positive electrode slurry on the current collector.

[0055] In some embodiments, the drying environment is a vacuum environment, the drying temperature is 60°C-150°C, for example, it can be 60°C, 70°C, 80°C, 90°C, 100°C, 110°C, 120°C, 130°C, 140°C, 150°C, etc., and the drying time is 12h-24h, for example, it can be 12h, 13h, 14h, 15h, 16h, 17h, 18h, 19h, 20h, 21h, 22h, 23h, 24h, etc.

[0056] In a seventh aspect, an embodiment of the present application provides a lithium-ion battery, comprising:

[0057] The above-mentioned positive electrode;

[0058] The electrolyte comprises lithium hexafluorophosphate and an organic solvent.

[0059] In some embodiments, the organic solvent includes one or more of ethylene carbonate, methylpropyl carbonate, propylene carbonate, butylene carbonate, dimethyl carbonate, diethyl carbonate, or ethyl methyl carbonate.

[0060] In some embodiments, the molar ratio of the lithium carbonate to the lithium hexafluorophosphate is (0.001-0.1):1, for example, it can be 0.001:1, 0.005:1, 0.007:1, 0.01:1, 0.02:1, 0.03:1, 0.04:1, 0.05:1, 0.06:1, 0.07:1, 0.08:1, 0.09:1, 0.1:1, etc. In an eighth aspect, an embodiment of the present application provides a method for preparing a lithium ion battery, comprising the following steps:

[0061] A lithium-ion battery preform and an electrolyte are provided. The lithium-ion battery preform comprises a packaged negative electrode plate, the positive electrode plate, a separator and a battery shell. The electrolyte is injected into the lithium-ion battery preform, and after standing at a set temperature, the preform is formed and divided to obtain a lithium-ion battery. The electrolyte comprises lithium hexafluorophosphate and an organic solvent.

[0062] In the present application, during the standing process, the lithium carbonate on the surface of the positive electrode active material reacts with the lithium hexafluorophosphate in the electrolyte, thereby in-situ generating a lithium difluorophosphate coating layer on the surface of the positive electrode active material.

[0063] In some embodiments, the set temperature is 40°C-80°C, for example, 40°C, 45°C, 50°C, 55°C, 60°C, 65°C, 70°C, 75°C, 80°C, etc., and the standing time is 12h-96h, for example, 12h, 20h, 30h, 40h, 50h, 60h, 70h, 80h, 90h, 96h, etc. At the temperature and standing process, the lithium carbonate on the surface of the positive active material and the lithium hexafluorophosphate in the electrolyte can fully react, and a layer of lithium difluorophosphate coating is generated in situ on the surface of the positive active material. If the temperature is too high and the standing time is too long, the electrolyte is prone to decomposition.

[0064] Example 1

[0065] A method for preparing a positive electrode slurry comprises the following steps:

[0066] Under the condition of a dew point of -55°C, lithium nickel cobalt manganese oxide and lithium carbonate (particle size of 0.05 μm-0.5 μm, of which the volume fraction of 0.1 μm-0.3 μm particles is 50%) are mixed and ball-milled at a mass ratio of 1:0.003 for 4 hours at a rotation speed of 80 r / min to obtain a pretreated positive electrode active material;

[0067] The pretreated positive electrode active material, polyvinylidene fluoride (PVDF), conductive carbon black (SP) and polyacrylic acid were mixed in N-methylpyrrolidone (NMP) at a mass ratio of 96.5:2.0:1.3:0.2 to obtain a positive electrode slurry.

[0068] A method for preparing a positive electrode sheet comprises the following steps:

[0069] The positive electrode slurry was coated on the current collector aluminum foil and vacuum dried at 110°C for 18 h to obtain a positive electrode sheet (single-sided surface density of 200 g / m 2 ).

[0070] A method for preparing a lithium ion battery comprises the following steps:

[0071] The positive electrode sheet, the graphite negative electrode sheet, the PE separator and the battery shell are rolled, cut, stacked and packaged to obtain a lithium-ion battery preform;

[0072] After injecting an electrolyte (including lithium hexafluorophosphate and an organic solvent composed of ethylene carbonate, dimethyl carbonate, diethyl carbonate, and ethyl methyl carbonate) into a lithium ion battery preform, the preform is allowed to stand at 60° C. for 24 hours, so that the lithium carbonate on the surface of the positive electrode active material reacts with the lithium hexafluorophosphate in the electrolyte to generate lithium difluorophosphate, and then the lithium ion battery is obtained through chemical formation and volume separation, wherein the molar ratio of lithium hexafluorophosphate to lithium carbonate is 1:0.06.

[0073] Example 2

[0074] This embodiment is substantially the same as Embodiment 1, except that the mass ratio of lithium nickel cobalt manganese oxide to lithium carbonate in this embodiment is 1:0.01.

[0075] Example 3

[0076] This embodiment is basically the same as Embodiment 1, except that, in this embodiment, lithium nickel cobalt manganese oxide is replaced with lithium iron phosphate, and the mass ratio of lithium iron phosphate to lithium carbonate is 1:0.008.

[0077] Example 4

[0078] This embodiment is basically the same as Embodiment 1, except that, in this embodiment, lithium nickel cobalt manganese oxide is replaced with lithium iron phosphate, and the mass ratio of lithium iron phosphate to lithium carbonate is 1:0.012.

[0079] Example 5

[0080] This embodiment is substantially the same as Embodiment 1, except that the volume fraction of particles with a particle size of 0.1 μm-0.3 μm in the lithium carbonate in this embodiment is 40%.

[0081] Example 6

[0082] This embodiment is substantially the same as Embodiment 1, except that the volume fraction of particles with a particle size of 0.1 μm-0.3 μm in the lithium carbonate in this embodiment is 60%.

[0083] Example 7

[0084] This embodiment is substantially the same as Embodiment 1, except that in this embodiment, the mass ratio of the pretreated positive electrode active material, PVDF, SP and polyacrylic acid is 98:0.8:0.8:0.4.

[0085] Example 8

[0086] This embodiment is substantially the same as Embodiment 1, except that the mass ratio of the pretreated positive electrode active material, PVDF, SP and polyacrylic acid in this embodiment is 94:3:2.5:0.5.

[0087] Example 9

[0088] This embodiment is substantially the same as embodiment 1, except that the ball milling time in this embodiment is 2 h.

[0089] Example 10

[0090] This embodiment is substantially the same as embodiment 1, except that the ball milling time in this embodiment is 8 h.

[0091] Embodiment 11

[0092] This embodiment is substantially the same as Embodiment 1, except that the standing temperature in this embodiment is 40°C.

[0093] Example 12

[0094] This embodiment is substantially the same as Embodiment 1, except that the standing temperature in this embodiment is 80°C.

[0095] Embodiment 13

[0096] This embodiment is substantially the same as Embodiment 1, except that the standing time in this embodiment is 12 hours.

[0097] Embodiment 14

[0098] This embodiment is substantially the same as Embodiment 1, except that the standing time in this embodiment is 96 hours.

[0099] Embodiment 15

[0100] This embodiment is substantially the same as Embodiment 1, except that the ratio of lithium hexafluorophosphate to lithium carbonate in this embodiment is 1:0.1.

[0101] Example 16

[0102] This embodiment is substantially the same as Embodiment 1, except that the ratio of lithium hexafluorophosphate to lithium carbonate in this embodiment is 1:0.001.

[0103] Embodiment 17

[0104] This comparative example is substantially the same as Example 1, except that the molar ratio of lithium hexafluorophosphate to lithium carbonate is 1:0.3.

[0105] Comparative Example 1

[0106] This comparative example is substantially the same as Example 1, except that lithium carbonate is not used in this comparative example.

[0107] Comparative Example 2

[0108] This comparative example is substantially the same as Example 3, except that lithium carbonate is not used in this comparative example.

[0109] Comparative Example 3

[0110] This comparative example is substantially the same as Example 2, except that lithium carbonate is not used in this comparative example, the mass ratio of lithium hexafluorophosphate to lithium difluorophosphate in the electrolyte is 97:3, and the mass of lithium difluorophosphate is consistent with the theoretical production amount of lithium difluorophosphate in Example 2.

[0111] Comparative Example 4

[0112] This comparative example is substantially the same as Example 1, except that the mass ratio of lithium nickel cobalt manganese oxide to lithium carbonate in this comparative example is 1:0.1.

[0113] Test example:

[0114] Surface alkalinity test method: Under a vacuum degree of 0.01pa, the pretreated positive electrode active material (positive electrode active material with lithium carbonate coated on the surface) is heated to 1023K and then heat treated for 2h to fully decompose the Li2CO3 on the surface of the material to generate Li2O; then CO2 is used as the acidic adsorption molecule at 423K, and the adsorption amount of CO2 is tested using a heat flow micro-adsorption calorimeter, and the adsorption amount is recorded as the surface alkalinity.

[0115] Ion chromatography test method: Take a 2cm*2cm size of the positive electrode after standing, place it in 10ml acetonitrile and soak it for 4 hours, filter the soaking liquid, take 1ml of the above filtrate and dilute it 10 times, take 5ml of the dilution and test it with ion chromatography, and get the characteristic peak intensity of 7 to 9min. The detection conditions of ion chromatography are as follows: the chromatographic column is an anion chromatographic column, the mobile phase is 3.6mmol / L sodium carbonate solution (the solvent is acetonitrile aqueous solution with a volume concentration of 40%), and the detector is a conductivity detector.

[0116] Lithium-ion battery discharge DC resistance (DCR) test method: Charge the battery to 100% SOC at 1 / 3 at 25°C, then discharge it to 50% SOC at 1 / 3, then let it stand for 60 minutes, record the voltage V1 at the beginning of discharge, then discharge at 2C current I for 10 seconds and record the sampled voltage V2 at the end of discharge. The battery's discharge DCR = (V2-V1) / I.

[0117] Lithium-ion battery cycle performance test method: At 45°C, the lithium-ion battery is charged and discharged 500 times at a constant current rate of 1.0C (nominal capacity). The capacity retention rate after 500 cycles (C%) = (discharge capacity of the 500th cycle / first discharge capacity) × 100%.

[0118] The test data is shown in Table 1:

[0119]

[0120] From Table 1, we can see that:

[0121] Compared with Example 2, and compared with Example 4, in Example 3, the mass of lithium carbonate increases, the measured surface alkalinity increases, the characteristic peak intensity increases, the battery resistance decreases, and the capacity retention rate increases. Compared with Example 1, Example 5, and Example 6, the volume fraction of particles with an average particle size of 0.1μm-0.3μm in lithium carbonate increases, the measured surface alkalinity increases, the characteristic peak intensity increases, the battery resistance decreases, and the capacity retention rate increases. Compared with Example 1, Example 11, and Example 12, the standing temperature increases, the measured battery resistance decreases, and the capacity retention rate increases. Compared with Example 1, Example 13, and Example 14, the standing time increases, the battery resistance decreases, and the capacity retention rate increases. Compared with Example 1, Example 15, Example 16, and Example 17, the mass of lithium carbonate increases, the measured battery resistance increases, and the capacity retention rate increases.

[0122] Compared with Comparative Example 1 and Comparative Example 2, respectively, the lithium ion batteries of Example 1 and Example 3 have lower discharge DC resistance (DCR) and higher capacity retention rate. It can be seen that the present application can reduce the electrode / electrolyte interface impedance, improve the cycle stability of the battery, and enhance the battery performance by in-situ generating a layer of lithium difluorophosphate coating on the surface of the positive electrode active material.

[0123] The mass of lithium difluorophosphate added in Comparative Example 3 is the same as the mass of lithium difluorophosphate generated in Example 2, but compared with Comparative Example 3, the lithium ion battery of Example 2 has a lower discharge DC resistance (DCR) and a higher capacity retention rate. The reason is that the lithium difluorophosphate added in Comparative Example 3 causes the viscosity of the electrolyte to increase, thereby reducing its effect of improving the performance of the battery. The present application generates a layer of lithium difluorophosphate coating in situ on the surface of the positive electrode active material, which can increase the amount of lithium difluorophosphate generated, but it will not cause the viscosity of the electrolyte to increase, thereby effectively improving the cycle stability of the battery and enhancing the battery performance.

[0124] Compared with Comparative Example 4, the lithium ion batteries of Examples 1 and 2 have lower discharge DC resistance (DCR) and higher capacity retention rate. The reason is that the amount of lithium carbonate used in Comparative Example 4 is too large, and unreacted lithium carbonate may exist, which leads to increased internal resistance of the battery and decreased cycle performance.

[0125] from Figure 1 It can be seen that the ion chromatogram of the positive electrode plate soaking solution after high-temperature standing in the present application shows an obvious characteristic peak at a retention time of 7 to 9 minutes, which is the characteristic peak of lithium difluorophosphate, and Figure 1 The peak height is 46 μS·cm -1 , indicating that lithium difluorophosphate is generated. The characteristic peak intensity of lithium difluorophosphate in the present application can be 10 to 400 μS·cm -1 .

[0126] The embodiments of the present invention are described in detail above. Specific examples are used herein to illustrate the principles and implementation methods of the present invention. The description of the above embodiments is only used to help understand the method of the present invention and its core idea. At the same time, for those skilled in the art, according to the idea of ​​the present invention, there will be changes in the specific implementation methods and application scope. In summary, the content of this specification should not be understood as a limitation on the present invention.

Claims

1. A positive electrode material used in a battery, wherein the battery comprises an electrolyte, wherein the electrolyte comprises lithium hexafluorophosphate, wherein: The positive electrode material includes a positive electrode active substance and lithium carbonate. The lithium carbonate is coated on the surface of the positive electrode active substance. The mass ratio of the positive electrode active substance to the lithium carbonate is 1:(0.001-0.03).

2. The positive electrode material according to claim 1, characterized in that The surface basicity of the positive electrode material is 80 μmol·g -1 ~2000μmol·g -1 ; and / or The volume fraction of particles with an average particle size of 0.1 μm-0.3 μm in the lithium carbonate is at least 40%.

3. A method for preparing a positive electrode material, wherein the positive electrode material is used in a battery, wherein the battery comprises an electrolyte, and wherein the electrolyte comprises lithium hexafluorophosphate, wherein: The preparation method comprises the following steps: A positive electrode active material and lithium carbonate are provided, and the lithium carbonate is coated on the surface of the positive electrode active material to obtain a positive electrode material.

4. The method for preparing the positive electrode material according to claim 3, characterized in that: The step of coating the lithium carbonate on the surface of the positive electrode active material comprises: The lithium carbonate and the positive electrode active material are ball-milled.

5. The method for preparing the positive electrode material according to claim 4, characterized in that: The ball milling time is 2h-8h, and the rotation speed is 60r / min-120r / min; and / or The ball milling is carried out under the environmental condition of dew point temperature ≤-50°C.

6. A positive electrode slurry used in a battery, wherein the battery comprises an electrolyte, and the electrolyte comprises lithium hexafluorophosphate, characterized in that: The positive electrode slurry comprises: A positive electrode material as claimed in claim 1 or 2 or a positive electrode material prepared by the method for preparing a positive electrode material as claimed in any one of claims 3 to 5, and a binder and a conductive agent.

7. The positive electrode slurry according to claim 6, characterized in that: The positive electrode slurry also includes a dispersant, and the mass percentages of the positive electrode material, the binder, the conductive agent and the dispersant are (94-98): (0.8-5): (0.5-5): (0.1-0.5).

8. A positive electrode plate, used in a battery, wherein the battery comprises an electrolyte, wherein the electrolyte comprises lithium hexafluorophosphate, wherein: Comprising the positive electrode slurry as described in claim 6 or 7.

9. A lithium ion battery, characterized in that: include: The positive electrode plate and electrolyte as claimed in claim 8, wherein the electrolyte comprises lithium hexafluorophosphate and an organic solvent.

10. The lithium ion battery according to claim 9, characterized in that: The molar ratio of the lithium hexafluorophosphate to the lithium carbonate is 1:(0.001-0.1).

11. A method for preparing a lithium ion battery, characterized in that: The following steps are involved: A lithium-ion battery preform and an electrolyte are provided, wherein the lithium-ion battery preform comprises a packaged negative electrode plate, the positive electrode plate according to claim 8 or 9, a separator and a battery shell, and the electrolyte is injected into the lithium-ion battery preform, and a lithium-ion battery is obtained after standing. The electrolyte comprises lithium hexafluorophosphate and an organic solvent.

12. The method for preparing a lithium ion battery according to claim 11, characterized in that: The standing temperature is 40° C.-80° C., and the standing time is 12 h-96 h.

Citation Information

Cited By

  • Positive electrode material and preparation method therefor, positive electrode slurry, positive electrode sheet, and lithium ion battery and preparation method therefor

    EP4783258A1

  • Positive electrode material and preparation method therefor, positive electrode slurry, positive electrode sheet, and lithium ion battery and preparation method therefor

    WO2026056082A1